Sociodemographic Correlates of Organized Sports Participation in a Sample of Middle School Students in China - Ren, Tao; Yan, Jin; Sun, Qiang (Frontiers in Public Health, 2021)
Background: Organized sport participation (OSP) is regarded as an effective medium for promoting more physical activity. It is valuable to understand the correlates of OSP for developing effective physical activity intervention. Purpose: This study aims to explore the sociodemographic correlates of OSP among middle school students from the Nanjing City of China. Methods: A total of 7,097 adolescents (50.1% girls) aged 12–15 years from Nanjing City were recruited in this survey. Self-reported data on sex, grade, race, residence locations, proficient sport skills, and household highest education were obtained. OSP was assessed by the question asked in the questionnaire on whether participants were involved in any “sports club or team” with the binary answer options of “yes” and “no,” for statistical analysis purposes. Generalized linear models were used to determine the correlates of OSP. Results: Only 16.6% of adolescents reported to involve in any organized sport over the past year. Boys (OR = 1.34, 95%CI: 1.18–1.53) and 7th graders (OR = 1.40, 95%CI: 1.18–1.65) were more likely to participate in organized sport. Adolescents being Han ethnicity were less likely to participant in organized sport (OR = 0.60, 95%CI: 0.40–0.92), as were those with less (one or two) proficient sport skills (OR = 0.27, 95%CI:0.20–0.37 and OR = 0.43, 95%CI: 0.36–0.50, respectively). Besides, residence and household highest education were not significantly associated with OSP among recruited adolescents who are aged from 12 to 15 years. Conclusion: Sex, grades, race, and proficient sport skills were significant correlates of organized sports participation. School, community and family need to provide more resources and support for disadvantaged populations in organized sports participation.